Application of Titanium Dioxide 2017
DOI: 10.5772/intechopen.68710
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanotechnology in Agriculture: Assessment of TiO2 Nanoparticle Effects on Barley

Abstract: Many aspects associated with the application of nanotechnology to agricultural activities are still unknown. In particular, there is not enough information on nanotoxicology in crops and we do not know the fate of nanoparticles in crops. Multiple experiments were carried out to study the effects of titanium oxide nanoparticles (nTiO 2) on barley (Hordeum vulgare). Germinating seeds were exposed to 0, 500, 1000, and 2000 mg l −1 nTiO 2. Seed germination percentage, mitotic index, root elongation, and Ti concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(31 reference statements)
0
14
1
Order By: Relevance
“…The N, S, Ca, Fe, Mn, and Zn concentrations of barley seeds increased compared to the control treatment while K concentration decreased with TiO2-NP treatments. On the other hand, P, and Mg, B and Cu concentrations did not affect the incensement of TiO2-NP treatments (Mattiello & Marchiol 2017). Tan et al (2017) reported that the unmodified TiO2-NPs enhanced Cu (104%) and Fe (90%); hydrophilic TiO2-NPs enhanced Fe (90%).…”
Section: Mineral Nutrition Uptakementioning
confidence: 97%
“…The N, S, Ca, Fe, Mn, and Zn concentrations of barley seeds increased compared to the control treatment while K concentration decreased with TiO2-NP treatments. On the other hand, P, and Mg, B and Cu concentrations did not affect the incensement of TiO2-NP treatments (Mattiello & Marchiol 2017). Tan et al (2017) reported that the unmodified TiO2-NPs enhanced Cu (104%) and Fe (90%); hydrophilic TiO2-NPs enhanced Fe (90%).…”
Section: Mineral Nutrition Uptakementioning
confidence: 97%
“…The TiO 2 NPs are among the most used in the industry, and it is estimated that 0.13 to 1200 µg of TiO 2 NPs per kg of soil are incorporated each year [78]. Experimental tests to verify toxicity, transfer to ecosystems and their use as promoters of plant metabolism have also increased in number in recent years [79].…”
Section: Responses Of Plants To Nps and Nmsmentioning
confidence: 99%
“…The effect of ENP on plants has been investigated, and it is argued that the field of nanotechnology has excellent potential for the plant production systems (Mattiello & Marchiol, ; Prasad, Bhattacharyya, & Nguyen, ; Rastogi et al, ), with lower cost, energy, and wastes (Fraceto et al, ; Servin & White, ). In this sense, the term phytonanotechnology is used and could assist in the development of “smart” crops (Wang, Lombi, Zhao, & Kopittke, .…”
Section: Resultsmentioning
confidence: 99%
“…Especially for plant science, Mattiello and Marchiol () recognized two main groups of ENP: the carbon nanomaterial (CBNMs) and the metal‐based nanomaterials (MBNMs). In the last 3 years (2016–2018), 296 investigations were published in “Web of Science” related to the effect of ENPs on plants, but only 40 documents tie the term “nano” and “plant growth.” Other word combinations used in the search are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%